Modelling the uncertainty in monthly international tourist arrivals to the Maldives - Shareef, Riaz; McAleer, Michael (Tourism management (1982), 2007)
The Indian Ocean tsunami of 26 December 2004 made clear the devastating short term impact in lost lives, as well as the longer term impact in lost livelihoods and an uncertain future. Tourism was one of the more obvious non-human casualties of this tragic natural phenomenon. Tourism is the principal industry in the Maldives, accounting for more than 30% of GDP and more than 60% of foreign exchange earnings. As over 55% of government tax revenue arises from tourism-related taxes, and monthly government budget financing depends largely on international tourist arrivals, the monitoring of daily, weekly and monthly international tourist arrivals is essential for fiscal policy evaluation. Over 600,000 tourists visited the Maldives in 2004. This paper examines the time series properties of monthly international tourist arrivals to the Maldives from eight major tourist source countries, namely Italy, Germany, UK, Japan, France, Switzerland, Austria and the Netherlands, from 1 January 1994 to 31 December 2003. Monthly international tourist arrivals and the associated uncertainty are estimated for the eight principal tourist source countries. Univariate and multivariate time series models of conditional volatility (or uncertainty) are estimated and tested. The conditional correlations are estimated and examined to ascertain whether there is specialization, diversification or segmentation in the international tourism demand shocks from the major tourism source countries to the Maldives. The estimated static conditional correlations for monthly international tourist arrivals, as well as for the respective transformed series, were found to be significantly different from zero, but also relatively low. This indicates that the government of the Maldives and the major tour operators that organise tourist vacations have to emphasise their marketing efforts independently of each tourist source country.